Intraoperative Ergonomic Assessment of Exoscopes versus Conventional DIEP Flap - Wang, Tianke; Norasi, Hamid; Nguyen, Minh-Doan; Harless, Christin; Law, Katherine E.; Smith, Tianqi G.; Tetteh, Emmanuel; Hallbeck, Susan (Journal of Reconstructive Microsurgery, 2022)
Background This study compared the ergonomics of surgeons during deep inferior epigastric perforator (DIEP) flap surgery using either baseline equipment (loupes, headlights, and an operating microscope) or an exoscope. Plastic surgeons may be at high risk of musculoskeletal problems. Recent studies indicate that adopting an exoscope may significantly improve surgeon postures and ergonomics.Methods Postural exposures, using inertial measurement units at the neck, torso, and shoulders, were calculated in addition to the surgeons' subjective physical and cognitive workload. An ergonomic risk score on a scale of 1 (lowest) to 4 (highest) was calculated for each of the postures observed. Data from 23 bilateral DIEP flap surgeries (10 baseline and 13 exoscope) were collected.Results The neck and torso risk scores decreased significantly during abdominal flap harvest and chest dissection, while right shoulder risk scores increased during the abdominal flap harvest for exoscope DIEP flap procedures compared with. Exoscope anastomoses demonstrated higher neck, right shoulder, and left shoulder risk scores. The results from the survey for the “surgeon at abdomen” showed that the usage of exoscopes was associated with decreased performance and increased mental demand, temporal demand, and effort. However, the results from the “surgeon at chest” showed that the usage of exoscopes was associated with lower physical demand and fatigue, potentially due to differences in surgeon preference.Conclusion Our study revealed some objective evidence for the ergonomic benefits of exoscope; however, this is dependent on the tasks the surgeon is performing. Additionally, personal preferences may be an important factor to be considered in the ergonomic evaluation of the exoscope.
Keywords: exoscope; plastic surgery; ergonomics; postural exposure; inertial measurement unit